Hipotiroidisme Pada Proses Penuaan Dan Estetika - Ratna Shintia Defi (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2025)
Aging is a biological process that affects various bodily functions, with the endocrine system, particularly thyroid hormones, playing a crucial role in this process. Thyroid hormone dysregulation, especially hypothyroidism, commonly found in older adults, can accelerate signs of aging both physiologically and aesthetically. The decline in thyroid gland function leads to reduced thyroid hormone production, resulting in slowed metabolism, dry and rough skin, brittle hair, and decreased skin elasticity. Although the symptoms of hypothyroidism often overlap with common signs of aging, thyroid hormone replacement therapy can help restore bodily function and slow down the aging effects. This study aims to analyze the relationship between thyroid hormone dysregulation, particularly hypothyroidism, and the aging process, as well as its impact on physical appearance. This review shows that treating hypothyroidism can minimize its negative effects on body aesthetics and improve the quality of life in the elderly.